Hypoactivity of the central dopaminergic system and autistic-like behavior induced by a single early prenatal exposure to lipopolysaccharide - Kirsten, Thiago B.; Chaves-Kirsten, Gabriela P.; Chaible, Lucas M.; Silva, Ana C.; Martins, Daniel O.; Britto, Luiz R.G.; Dagli, Maria L. Z.; Torrao, Andrea S.; Palermo-Neto, Joao; Bernardi, Maria M. [UNESP] (Wiley-Blackwell, 2012)
The aim of the present study was to evaluate the behavioral patterns associated with autism and the prevalence of these behaviors in males and females, to verify whether our model of lipopolysaccharide (LPS) administration represents an experimental model of autism. For this, we prenatally exposed Wistar rats to LPS (100 mu g/kg, intraperitoneally, on gestational day 9.5), which mimics infection by gram-negative bacteria. Furthermore, because the exact mechanisms by which autism develops are still unknown, we investigated the neurological mechanisms that might underlie the behavioral alterations that were observed. Because we previously had demonstrated that prenatal LPS decreases striatal dopamine (DA) and metabolite levels, the striatal dopaminergic system (tyrosine hydroxylase [TH] and da receptors D1a and D2) and glial cells (astrocytes and microglia) were analyzed by using immunohistochemistry, immunoblotting, and real-time PCR. Our results show that prenatal LPS exposure impaired communication (ultrasonic vocalizations) in male pups and learning and memory (T-maze spontaneous alternation) in male adults, as well as inducing repetitive/restricted behavior, but did not change social interactions in either infancy (play behavior) or adulthood in females. Moreover, although the expression of da receptors was unchanged, the experimental animals exhibited reduced striatal TH levels, indicating that reduced da synthesis impaired the striatal dopaminergic system. The expression of glial cell markers was not increased, which suggests that prenatal LPS did not induce permanent neuroinflammation in the striatum. Together with our previous finding of social impairments in males, the present findings demonstrate that prenatal LPS induced autism-like effects and also a hypoactivation of the dopaminergic system. (c) 2012 Wiley Periodicals, Inc.
Keywords: animal model; autism-like effects; dopamine; gestation; infection